Thrombospondin-1 Receptor CD47 Overexpression Contributes to P-Glycoprotein-Mediated Multidrug Resistance Against Doxorubicin in Thyroid Carcinoma FTC-133 Cells - Courageot, Marie-Pierre; Duca, Laurent; Martiny, Laurent; Devarenne-Charpentier, Emmanuelle; Morjani, Hamid; El Btaouri, Hassan (Frontiers in Oncology, 2020)
It is now admitted that in addition to acquired resistance, the tumor microenvironment contributes to the development of chemo-resistance and malignant progression. In a previous study, we showed that Dox induced apoptosis in FTC-133 cells by trigging JNK pathway. This process was accompanied by a decrease of thrombospondin-1 (TSP-1) expression. Moreover, exogenous TSP-1 or its C-terminal-derived peptide interact with receptor CD47 and are able to protect FTC-133 cells against Dox-induced apoptosis. Here, we investigated the involvement of TSP-1/CD47 interaction in a context of acquired multidrug resistance in FTC-133 cells. To that end, we established a Dox-resistant cell line (FTC-133R cells) which developed a resistance against Dox-induced apoptosis. Cell viability was evaluated by Uptiblue assay, nuclear Dox was measured by microspectrofluorimetry, caspase activity was measured by fluorescence of cleaved caspase-3 substrate, gene expression was evaluated by RT-PCR and protein expression was examined by western-blot. Our results showed that FTC-133R overexpressed the P-gp and were 15-fold resistant to Dox. JNK phosphorylation and Dox-induced apoptosis were reduced in FTC-133R cells. Expression of CD47 was increased in FTC-133R cells but TSP-1 expression presented similar levels in two cell lines. VPL restored Dox nuclear uptake and FTC-133R cell sensitivity to apoptosis and induced a decrease in CD47 mRNA expression. Moreover, knockdown of CD47 in FTC-133R cells induced an increase in JNK activation and sensitized FTC-133R cells to Dox. Our data suggest that CD47 is able to contribute to the protection of FTC-133R cells against Dox-induced apoptosis and/or to potentiate the acquired Dox resistance.